The Effectiveness of GECB Pastille in Reducing Complications of Dry Socket Syndrome. (22nd April 2012) - Haghighat, Abbas; Bahri Najafi, Rahim; Bazvand, Mostafa; Badrian, Hamid; Khalighinejad, Navid; Goroohi, Hossein
Abstract : Background and Purpose . Dry socket syndrome is one of the most irritating complications after tooth extraction. This study aims to investigate the efficacy of pastille GECB compared to ZOE. Materials and Methods . 30 patients with dry socket syndrome were selected and divided into two groups. GECB pastille was produced with 3% Guaiacol, 3% Eugenol 1.6% Chlorobutanol, sized3 × 7 × 10  mm. GECB was applied in one group, and ZOE was used for the other group. Duration of pain after treatment and painkiller intake values were recorded within 20 days. The data were analyzed with independent samples t -test, Mann-Whitney, and Chi-Square tests. Results . Pain persisted for45.53 ± 33.34 minutes in patients treated with ZOE and19.87 ± 21.80 minutes in those treated with GECB (P = 0.19 ). Patients in the ZOE group reported more painkiller intake within 20 days (P = 0.031 ). Conclusion . GECB showed more significant efficacy in reducing complications after tooth extraction.